Structure and dielectric properties of lead-free BaSn0.1Ti 0.9O3-BaFe0.5Nb0.5O3 ceramics - Kantha P. (2014)
Binary solid solutions of the (1-x)BaSn0.1Ti0.9O 3-xBaFe0.5Nb0.5O3 system, with x = 0, 0.05, 0.10, 0.15 and 0.20 were prepared via a solid-state processing technique. The BST and BFN powders were synthesized separately using a calcination technique with optimum temperature. XRD results revealed that the structures of the BST-BFN ceramics were of tetragonal symmetry and the tetragonality (c/a ratio) decreased with increasing BFN content. BFN caused enhanced dielectric constant of BST ceramics that increased with temperature. The highest dielectric constant was ∼120000 for x = 0.20 at temperature of 400°C (1 kHz). © 2014 Copyright Taylor and Francis Group, LLC.